Epigenetics and Responsibility Ethical Perspectives - Moormann, Emma; Smajdor, Anna; Cutas, Daniela (Bristol University Press, 2024)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation.